2018
DOI: 10.1074/jbc.ra118.002426
|View full text |Cite
|
Sign up to set email alerts
|

Angiopoietin-like 4 promotes the intracellular cleavage of lipoprotein lipase by PCSK3/furin in adipocytes

Abstract: Lipoprotein lipase (LPL) catalyzes the breakdown of circulating triglycerides in muscle and fat. LPL is inhibited by several proteins, including angiopoietin-like 4 (ANGPTL4), and may be cleaved by members of the proprotein convertase subtilisin/kexin (PCSK) family. Here, we aimed to investigate the cleavage of LPL in adipocytes by PCSKs and study the potential involvement of ANGPTL4. A substantial portion of LPL in mouse and human adipose tissue was cleaved into N- and C-terminal fragments. Treatment of diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
51
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(56 citation statements)
references
References 52 publications
4
51
1
Order By: Relevance
“…It was previously proposed that ANGPTL4 inhibits LPL mainly in the subendothelial space, close to the site where both proteins are produced (40). Recent evidence suggests, however, that intracellular degradation of LPL may also be promoted by the ANGPTL4 protein (41,42). This makes ANGPTL4 an autocrine/paracrine regulator of LPL, which is unable to inactivate LPL when the enzyme has reached GPIHBP1 on the basal side of the capillary endothelium (10,37).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was previously proposed that ANGPTL4 inhibits LPL mainly in the subendothelial space, close to the site where both proteins are produced (40). Recent evidence suggests, however, that intracellular degradation of LPL may also be promoted by the ANGPTL4 protein (41,42). This makes ANGPTL4 an autocrine/paracrine regulator of LPL, which is unable to inactivate LPL when the enzyme has reached GPIHBP1 on the basal side of the capillary endothelium (10,37).…”
Section: Discussionmentioning
confidence: 99%
“…The low levels of ANGPTL4, still present in the cells, may form inactive complexes with ANGPTL8, whose expression is greatly increased (6,7,38). The ANGPTL4/ANGPTL8 complex may be unable to promote the intracellular degradation of LPL and thus allow more LPL to be secreted by WAT, but the precise mechanism for this process remains unclear (41,42). Because of the decreased levels of ANGPTL4 in the subendothelial space, LPL can reach GPIHBP1 and the luminal side of the capillaries and hydrolyze TGs from VLDLs and chylomicrons.…”
Section: Discussionmentioning
confidence: 99%
“…LPL is widely expressed in muscle and capillary endothelial cells in adipose tissue, and serves an important role in fat metabolism by catalyzing the breakdown of chylomicrons and low-density lipoproteins into glycerol and free fatty acids (23). Previous studies have demonstrated that insulin reduces chylomicron levels in the blood by enhancing the activity of LPL and inhibits hormone-sensitive lipase in lipocytes to decrease the breakdown of lipocytes and the production of TG (11).…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that the Nterminal helix domain of ANGPTL4 can bind to LPL and change it from active dimers to form inactive monomers [33]. In addition, ANGPTL4 can also reduce the secretion of LPL in adipocytes [34][35][36].…”
Section: Interaction Between Angptl4 and Angptl8mentioning
confidence: 99%